PARK16 is associated with PD in the Malaysian population. Issue 6 (13th May 2016) - Gopalai, Aroma Agape; Ahmad‐Annuar, Azlina; Li, Hui‐Hua; Zhao, Yi; Lim, Shen‐Yang; Tan, Ai Huey; Lim, Thien Thein; Eow, Gaik Bee; Santhi, Puvanarajah; Shanthi, Viswanathan; Norlinah, Mohamed Ibrahim; Aziz, Zariah Abdul; et al.
Abstract : PARK16 was identified as a risk factor for Parkinson's disease in a Japanese cohort; however, subsequent studies in the other populations including the Chinese, European, Caucasian, and Chilean have shown a protective role instead. To investigate this locus in our Malaysian cohort, 1, 144 individuals were screened for five SNPs in the PARK16 locus and logistic regression analysis showed that the A allele of the rs947211 SNP reduced the risk of developing PD via a recessive model (Odds ratio 0.57, P ‐value 0.0003). Pooled analysis with other Asian studies showed that A allele of the rs947211 SNP decreased the risk of developing PD via a recessive model (Odds ratio 0.71, P ‐value 0.0001). In addition, when meta‐analysis was performed with other Asian population, three SNPs (rs823128, rs823156, and rs11240572) reduced risk of developing PD via a dominant model. © 2016 Wiley Periodicals, Inc.